Effect of alkalization time on the toughness and strength of jute sack waste lamina composite as an alternative car bumper material - Heri, Yudiono; Siregar, Januar Parlaungan; Sarwi, Asri; Hanif, Hidayat; Chikam, David Badi’ul; Aprilian, Johan Andric; Toni Agung, Supriyadi; Cionita, Tezara; Deni Fajar Fitriyana, . (Universiti Malaysia Pahang, 2024)
Alkaline conditions, such as the concentration of Sodium Hydroxide (NaOH) and the duration of soaking time, significantly affect the mechanical properties of natural fiber and its composites. The objective of this study is to investigate the effect of alkali treatment on the impact toughness and tensile strength of laminated composites made from jute sack (burlap) waste woven fibers, which can potentially be used as a substitute material for vehicle bumpers. The experimental group comprised specimens that were alkalized by manipulating the duration of soaking and the concentration of alkali in the woven fibers of jute sack waste, with a fiber orientation pattern of 0°/+90°/0°/+90°/0°. The fiber immersion time is 24 hours, 48 hours, and 72 hours when using a 5% NaOH concentration. Epoxy resin serves as a composite matrix, specifically epoxy resin and epoxy hardener. Two sets of specimens underwent tests to measure their tensile and impact strengths. The result of the study reveals that the jute sack laminated epoxy composite with a fiber orientation of 0°/+90°/0°/+90°/0° had the maximum tensile strength and impact strength after a 48-hour alkaline treatment at 14.99 MPa and 0.010 J/mm2, respectively. The alkali treatment has successfully enhanced the tensile strength of the jute fiber by approximately 42.49% and 39.66% when compared to the untreated jute fiber. The study concludes that the utilization of alkaline process with NaOH improves the surface area of the fiber, compatibility with polymer matrix and mechanical strength.